Perspectives of key stakeholders on the bi-national agreement between Argentina and Chile concerning the eradication of North American beavers and the restoration of affected ecosystems - Anderson, Christopher B; Roulier, Catherine; Pizarro, J Cristóbal (BOSQUE, 2017)
In 2008, Argentina and Chile signed an agreement to eradicate North American beavers (Castor canadensis) and restore degraded forests. The plans and actions related to this treaty have been conducted principally by experts with biological knowledge, paying scant attention to social aspects. From a socio-ecological approach, we evaluated the perspectives of two groups of key stakeholders (managers and researchers) from Argentinean and Chilean institutions. Via surveys, we compared i) attitudes towards the binational agreement’s two objectives (eradication and restoration), ii) the reasons that underlie these positions, and iii) the opinions about obstacles in implementing the agreement. The majority of both groups agreed with the two objectives, nonetheless managers supported more the eradication of the beaver and researchers supported more the restoration of degraded forests. These positions were based on biological arguments (e.g., ecological harm, being an exotic species), more than on social ones (e.g., ethics, economic impact). Paradoxically, managers and researchers identified the lack of information on social topics (e.g., internal management, interinstitutional cooperation, financing) as the main obstacle for the implementation of the agreement. While there was a high level of consensus, dissident positions were found among these stakeholders, whose profile is rather homogeneous. Managers particularly emphasized politico-institutional topics. Consequently, we are called upon to deepen and increase attention towards social dimensions in the approach to biological invasions to diversify the perspectives towards the problem, as well as to optimize and improve outcomes of potential actions in complex and heterogeneous societies.